2016
DOI: 10.1111/ejn.13211
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar brain inhibition in the target and surround muscles during voluntary tonic activation

Abstract: Motor surround inhibition is the neural mechanism that selectively favors the contraction of target muscles and inhibits nearby muscles to prevent unwanted movements. This inhibition was previously reported at the onset of a movement, but not during a tonic contraction. Cerebellar brain inhibition (CBI) is reduced in active muscles during tonic activation; however, it has not been studied in the surround muscles. CBI was evaluated in the first dorsal interosseus (FDI) as the target muscle, and the abductor dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…With the established paired-coil protocol ( 8 ), we found that the baseline CBI in the healthy elder subjects was less consistent than the young subjects [84.7 ± 14.9% (Figure 3 ) vs. 78.4 ± 3.1% ( 13 )]. CBI has been supposed to play an important role in selective tonic muscle movement, probably through a topographically specific reduction of inhibition in M1 ( 38 ). The fact that CBI showed a less consistence in the elder subjects might reflex a physiological feature of the aging process in humans.…”
Section: Discussionmentioning
confidence: 99%
“…With the established paired-coil protocol ( 8 ), we found that the baseline CBI in the healthy elder subjects was less consistent than the young subjects [84.7 ± 14.9% (Figure 3 ) vs. 78.4 ± 3.1% ( 13 )]. CBI has been supposed to play an important role in selective tonic muscle movement, probably through a topographically specific reduction of inhibition in M1 ( 38 ). The fact that CBI showed a less consistence in the elder subjects might reflex a physiological feature of the aging process in humans.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, compound movements were impaired and eliminated [96]. A recent study showed that a PC inhibited and disinhibited an activity of a selective muscle, but not in surrounding muscles, allowing execution of movement performed with a small number of muscles [97]. These findings point to an impairment in coordinating multiple degrees of freedom or synergy.…”
Section: Synergymentioning
confidence: 98%
“…For instance, tonic muscle contraction reduces the amount of CBI (Pinto et al, 2001) only for the activated muscle, but not for the surrounding ones (Panyakaew et al, 2016). This suggests that the CBI measurement and the CB activation during movement are somatotopic specific.…”
Section: Cerebellum-cerebral Cortex As Example Of Tms-tmsmentioning
confidence: 99%